Arranjos produtivos locais e projetos curriculares de cursos superiores na área de alimentos - Faria, Fellipe Jaculi Valdisser (2019)
Under analytical conception to improve regional development through investments in professional education, this dissertation belongs to the research line about Media, Education and Communication by the Post-Graduate Program in Technologies, Communication and Education, in Faculty of Education, at Federal University of Uberlândia, Minas Gerais, Brazil. It was established as general objective to analyze the training proposal of federal higher level courses, in food sector, offered in Uberaba-MG city depending on the dynamics of the productive sector. Considering the given problem: the extent to which the curriculum proposal of the Technology (IFTM) and Food Engineering (UFTM) provides for communication between education and the city’s employer society, the research was directed by the following specific objectives: to rescue of public policies for Brazilian professional education; describe the Local Productive Arrangements (APLs) in state of Minas Gerais, identifying professional conditions in the food sector in Uberaba; to analyze curricular components of the pedagogical project of the chosen courses; and, finally, to correlate the menus of these disciplines with the uberabian food labor market. As a guiding thread, the sociological argument about the humanizing function of the school (SACRISTÁN; PÉREZ GÓMEZ, 1998) and its consequent interaction with the reality (VASCONCELLOS, 2010) in social processes of the world of work, is based on historical-critical theory (MÉSZÁROS, 2005). In interdisciplinary focus, this investigation has presented an analysis of a quantitative and qualitative, descriptive and exploratory approach, following the path of knowledge production through a bibliographical review about notes in Brazilian political discourse regarding vocational education, a bibliographical research about the APLs in Minas Gerais and, notably, on data and professional conditions from Uberaba-MG. Associated with these units of analysis, formal alternatives of higher education courses were presented in this city, within the same area of Food, in two public educational institutions: the technologist’s degree, at the Federal Institute of Education, Science and Technology of the Triângulo Mineiro (IFTM), and the bachelor's degree, at the Federal University of the Triângulo Mineiro (UFTM). Also, according to the Critical Curricular Theory (MOREIRA, TOMAZ, 2011) and in the light of the professional considerations that were gathered to carry out documental bibliographic research of the subjects of each pedagogical project of the course (PPC), a cross-reference was made between the formative structure offered by the courses and the productive arrangement as a whole. In order to place education in the world of work, the present study has highlighted socioeconomic evidence that recognizes the above mentioned city as a potential productive pole in the food sector. From discussions, not only requiring greater involvement of state and municipal government managers, but, especially, by suggesting to the IFES that they are expected to advance in the interaction of the curriculum training structure of each course based on the productive dynamics in the labor market of Uberaba-MG.